Cover Feature: Hydrogen‐Bonding Interactions in the Ley–Griffith Oxidation: Practical Considerations for the Synthetic Chemist (Eur. J. Org. Chem. 2‐3/2019). Issue 2 (27th December 2018) - Moore, Peter W.; Zerk, Timothy J.; Burns, Jed M.; Bernhardt, Paul V.; Williams, Craig M.
Abstract : The Cover Feature shows the catalytic cycle of the Ley–Griffith oxidation, which like the site of the upcoming Heron8 conference on reactive intermediates and unusual molecules being held at Australia's iconic Uluru, works best under dry conditions. Extensive reaction monitoring has demonstrated that removal of product water by molecular sieves prevents sequestration of the co‐oxidant N ‐methylmorpholine oxide (NMO) and decomposition of the tetrapro‐pylammonium perruthenate (TPAP) catalyst, leading to practical recommendations for synthetic chemists. Cover design by Kylie Agnew‐Francis. More information can be found in the Communication by P. V. Bernhardt, C. M. Williams et al.